Strategi Pengembangan Usahatani Jagung Di Desa Baumata Kecamatan Taebenukabupaten Kupang . - Erma A. Tabelak; Sondang S. Pudjiastuti; Made Tusan Surayasa (Undana Press, 2019)
A Research on the Strategy for the Development of Maize Farming in Baumata Village, District of Taebenu, Kupang Regency has been carried out. Data collection was carried out in April-May 2018. This study aims to (1) find out the factors that influence the development of maize farming, and (2) find out the strategy to develop mize farming in Baumata Village, Taebenu District, Kupang Regency. The data collection method used is the Survey Method. The location of the study was determined intentionally, while the respondents were set by Random Simple Proportional. The population of this study amounted to 80 people are maize farmers who are members of 4 farmer groups in the sample area. The number of respondents 44 people determined by the Slovin formula, distributed each of 11 people in each farmer group. The collected data was analyzed descriptively and SWOT analysis.The results showed that (1) the factors that influenced the development of maize farming in Baumata Village, Taebenua Subdistrict were the availability of labor and farming experience, the increasing demand for maize and the availability of affordable market access, (2) the strategy of developing maize farming in Baumata Village can be done by utilizing unmanaged land for maize farming, improving the quality of farmers in applying maize cultivation technology, and preparing production facilities.Based on the results of the study, it can be suggested that (1) the knowledge and skills of farmers in the application of new maize cultivation technology need to be improved, (2) it is expected that farmers want to use superior maize seeds, improve maize cultivation, use fertilizers, and control pests and diseases Penelitian tentang Strategi Pengembangan Usahatani Jagung di Desa Baumata Kecamatan Taebenu Kabupaten Kupang telah dilaksanakan.Pengumpulan data dilaksanakan pada bulan April-Mei 2018.Penelitian ini bertujuan untuk (1) mengetahui faktor-faktor yang mempengaruhi pengembangan usahatani jagung, dan (2) mengetahui strategi untuk mengembangkan usahatani jagung di Desa Baumata Kecamatan Taebenu Kabupaten KupangMetode pengumpulan data yang digunakan adalah Metode Survei.Lokasi penelitian ditetapkan secara sengaja, Sedangkan responden ditetapkan secara Proporsional Acak Sederhana. Populasi penelitian ini berjumlah 80 orang adalah petani jagung yang tergabung dalam 4 buah kelompok tani yang ada di wilayah sampel. Jumlah responden 44 orang ditetapkan dengan rumus Slovin, terdistribusi masing-masing 11 orang di setiap kelompok tani. Data yang terkumpul dianalisis secara deskriptif dan analisis SWOT.Hasil penelitian menunjukkan bahwa (1) faktor-faktor yang mempengaruhi pengembangan usahatani jagung di Desa Baumata Kecamatan Taebenua adalah ketersediaan tenaga kerja dan pengalaman berusahatani, permintaan jagung yang terus meningkat dan adanya akses pasar yang terjangkau, (2) strategi pengembangan usahatani jagung di Desa Baumata dapat dilakukan dengan memanfaatkan lahan yang belum dikelola untuk usahatani jagung, meningkatkan kualitas petani dalam penerapan teknologi budidaya jagung, dan menyiapkan sarana produksinya.Hasil penelitian dapat disarankan bahwa (1) pengetahuan dan ketrampilan petani dalam penerapan teknologi baru budidaya jagung perlu ditingkatkan, (2) diharapkan petani mau menggunakan benih jagung unggul, memperbaiki cara bercocoktanam jagung, menggunakan pupuk, dan melakukan pengendalian hama dan penyakit.